The Discrimination and Tolerance as aeen in Andrzej Sapkowski’s The Witcher - Amelia Yuli Astuti; Rama Alan Nuari (Fakultas Sastra Universitas Ekasakti, 2025)
This research explores the themes of discrimination and tolerance in The Witcher series by Andrzej Sapkowski. Employing postcolonial theories by Edward Said, Homi K. Bhabha, and Gayatri Spivak, the study analyzes how fantasy narratives reflect social realities regarding injustice and diversity. The novel presents a fictional world marked by racial tensions among humans, elves, dwarves, and other magical beings. Through character interactions and the social structures depicted in the story, readers are presented with portrayals of marginalization, stereotyping, and systems of oppression. At the same time, the novel also includes moments of tolerance that suggest the possibility of coexistence and mutual understanding. This research uses a descriptive qualitative method with a library research approach. The findings reveal that The Witcher serves not only as a reflection of social inequality but also as a critique of dominant power structures and an exploration of efforts to build tolerance within a divided society.